IdentifyTPN: a tool for the identification of Time Petri nets. Issue 1 (July 2017) - Basile, F.; Chiacchio, P.; Coppola, J.
Abstract: Despite of the fact that the field of system identification of discrete event processes/systems has attracted the attention of many researchers in the last decade, there is a lack of tools that allow the use of the existing algorithms, alone or combined, in a unified environment. In this paper IdentifyTPN is presented, a tool developed by the Automatic Control Group of the University of Salerno, to solve a number of identification problems using Time Petri net models and algorithms, alone or combined, presented in the literature by the authors. The tool is available free of charge for interested readers.